2008
DOI: 10.1073/pnas.0802463105
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-engineered endothelial and epithelial implants differentially and synergistically regulate airway repair

Abstract: The trilaminate vascular architecture provides biochemical regulation and mechanical integrity. Yet regulatory control can be regained after injury without recapitulating tertiary structure. Tissue-engineered (TE) endothelium controls repair even when placed in the perivascular space of injured vessels. It remains unclear from vascular repair studies whether endothelial implants recapitulate the vascular epithelial lining or expose injured tissues to endothelial cells (ECs) with unique healing potential becaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 33 publications
2
49
0
1
Order By: Relevance
“…In this study, the promotion of scar tissue formation using a fibrin hydrogel sealant and the resulting resizing of the lung enhanced the respiratory function without the major trauma usually associated with surgery. However, recent findings have shown that regeneration of the damaged airways is regulated by multiple cell types and processes, dependent on the synergistic interactions between the different cell types present in lung tissue (170). These results reinforce the concept that the use of adequate cell types displaying appropriate phenotype could improve engineered lung function and promote organotypic tissue regeneration.…”
Section: Increasing the Complexity Of Tissue-engineered Lung Modelssupporting
confidence: 74%
“…In this study, the promotion of scar tissue formation using a fibrin hydrogel sealant and the resulting resizing of the lung enhanced the respiratory function without the major trauma usually associated with surgery. However, recent findings have shown that regeneration of the damaged airways is regulated by multiple cell types and processes, dependent on the synergistic interactions between the different cell types present in lung tissue (170). These results reinforce the concept that the use of adequate cell types displaying appropriate phenotype could improve engineered lung function and promote organotypic tissue regeneration.…”
Section: Increasing the Complexity Of Tissue-engineered Lung Modelssupporting
confidence: 74%
“…50,51 A similar approach has been used in the vascularization of the epithelium. 52 In the case of the epithelium, the interactions between the mesenchymal and epithelial cells are essential for tissue function in most organs. For example, sequential and reciprocal interactions between the stem cells and the epithelial cells are required for tooth development.…”
Section: Effect Of Heterotypic Interactions On Epithelial Cellsmentioning
confidence: 99%
“…Fortuitously, fibril formation can be replicated in a laboratory environment, 5 which can aid development of synthetic collagen-based scaffolds for tissue repair and regeneration applications. 6,7 Strategies for developing such scaffolds require controlled collagen assembly for reliable function, including control over packing density, elastic deformability, and the final size of the construct. These factors can affect bioactivity through mechanical response, or as a result of bioavailability issues arising from the porosity of the material.…”
Section: Introductionmentioning
confidence: 99%